Competitive Strategies for Womenpreneurs in Tasikmalaya City During The Covid-19 Pandemic - Nurfitriya, Mira; Koeswandi, Tika Annisa; Rachmani, Nizza Nadya; Widyawati, Retno Febriyastuti (Fakultas Pendidikan Ekonomi dan Bisnis, 2021)
This research is motivated by the current dual role of women, both as housewives and career women who seek income and are tested for their resilience and competitiveness in the face of the current global COVID-19 pandemic. Based on the pre-research data we obtained, women make a significant contribution to the economy of the City of Tasikmalaya, where more than 50% of MSME actors in the City of Tasikmalaya are female. This research itself aims to provide a general description of the opportunities faced by womenpreneurs in the City of Tasikmalaya, as well as to study further about what challenges are faced by womenpreneurs in the City of Tasikmalaya. The object of the research is womenpreneurs SMEs located in the city of Tasikmalaya. This study uses a qualitative approach with a descriptive method, where the analytical tool used for the data obtained is the SWOT analysis. The technique of collecting data is by using observation techniques, in-depth interviews, and literature studies. The results of this study are based on the Internal Factor Evaluation (IFE) and External Factor Evaluation (EFE) matrices, the position of Womenpreneur in Tasikmalaya City [IFE 3.101, EFE 3.037] is in Quadrant I.